Heidelberg neuro-music therapy restores attention-related activity in the angular gyrus in chronic tinnitus patients - Krick, Christoph Maria; Grapp, Miriam; Plinkert, Peter K. (Frontiers in neuroscience, 2017)
Background: Tinnitus is the perception of a phantom sound without external acoustic stimulation. Recent tinnitus research suggests a relationship between attention processes and tinnitus-related distress. It has been found that too much focus on tinnitus comes at the expense of the visual domain. The angular gyrus (AG) seems to play a crucial role in switching attention to the most salient stimulus. This study aims to evaluate the involvement of the AG during visual attention tasks in tinnitus sufferers treated with Heidelberg Neuro-Music Therapy (HNMT), an intervention that has been shown to reduce tinnitus-related distress., Methods: Thirty-three patients with chronic tinnitus, 45 patients with recent-onset tinnitus, and 35 healthy controls were tested. A fraction of these (21/21/22) were treated with the “compact” version of the HNMT lasting 1 week with intense treatments, while non-treated participants were included as passive controls. Visual attention was evaluated during functional Magnet-Resonance Imaging (fMRI) by a visual Continous Performance Task (CPT) using letter-based alarm cues (“O” and “X”) appearing in a sequence of neutral letters, “A” through “H.” Participants were instructed to respond via button press only if the letter “O” was followed by the letter “X” (GO condition), but not to respond if a neutral letter appeared instead (NOGO condition). All participants underwent two fMRI sessions, before and after a 1-week study period., Results: The CPT results revealed a relationship between error rates and tinnitus duration at baseline whereby the occurrence of erroneous “GO omissions” and the reaction time increased with tinnitus duration. Patients with chronic tinnitus who were treated with HNMT had decreasing error rates (fewer GO omissions) compared to treated recent-onset patients. fMRI analyses confirmed greater activation of the AG during CPT in chronic patients after HNMT treatment compared to treated recent-onset patients., Conclusions: Our findings suggest that HNMT treatment helps shift the attention from the auditory phantom percept toward visual cues in chronic tinnitus patients and that this shift in attention may involve the AG.
Gesehen am 07.06.2018